Battery thermal runaway propagation time delay strategy using phase change material integrated with pyro block lining: Dual functionality battery thermal design. (15th August 2023) - Talele, Virendra; Patil, Mahesh Suresh; Panchal, Satyam; Fraser, Roydon; Fowler, Michael
Abstract: In the view of the thermal runaway scenario phase change material are not capable to withstand thermal propagation phenomenon, hence it is important to provide a novel structure which can delay thermal runaway trigger point and not allows generated heat to propagate at faster rate from one cell to another. In this work, a series of numerical investigations are performed from cell to pack level configuration under heater assisted triggering method by providing a constant heat supply of 500 W until electrochemical kinetics of cell gets trigger. This setup is used to investigate, time delay and thermal propagation phenomenon by integrating submerged layer of phase change material. Conclusive evidence from investigation suggests that by integrating a submerged layer of phase change material, the thermal runaway trigger point can be effectively delayed. However, because phase change material is highly flammable in nature, heat propagates from one cell to another in a very short period, causing the entire pack to go into catastrophic thermal failure within short span of 10s. To delay this thermal propagation phenomenon and compliance GB 38031 and GB 38032 "national safety regulation of battery pack for Electric Bus and Electric Vehicle" that suggest once cell is trigger, neighbouring cell should not run in thermal runaway for at least 300s, we have optimized battery pack structural design by introducing low thermal conductive pyro liner at the wall of PCM. Results showed, this optimize design represents dual functionality of delaying thermal runaway trigger point of cell along with slowing down thermal propagation for at least 800s. Highlights: Thermal runaway propagation phenomenon is investigated for 75 Ah prismatic cell. Cell to Pack level thermal abuse modeling is simulated with heater-based cell triggering method. The catastrophic failure inside battery pack is monitored due to exothermic reactions by PCM. Dual functionality thermal design is proposed: Delaying thermal propagation as well as thermal runaway trigger point.